2014
DOI: 10.4049/jimmunol.1400433
|View full text |Cite
|
Sign up to set email alerts
|

Binding of AID to DNA Does Not Correlate with Mutator Activity

Abstract: The DNA deaminase AID initiates somatic hypermutation (SHM) and class switch recombination (CSR) by deaminating cytidines to uridines at variable region (V) genes and switch (S) regions. The mechanism by which AID is recruited to V genes and S region DNA is poorly understood. Here we have employed the CH12 B lymphoma line to demonstrate that while S regions can efficiently recruit AID and undergo mutations and deletions, AID neither binds to nor mutates the V gene, thus clearly demonstrating intra-immunoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…The overall mutation frequency did not differ significantly between wild type parental (WT) and Polb knockdown CH12-F3 cells (2.1 x10 -3 vs 2.5 x10 -3 , respectively, Table I). We found that mutations at A:T base pairs were infrequent in the WT CH12-F3 cells ( 9 out of 59363 sequenced A:T bps were mutated), in agreement with a previous study (Matthews et al, 2014). In contrast, Polb knockdown CH12-F3 cells showed a considerable number of A:T mutations (23 out of 57988 sequenced A:T bps were mutated.…”
Section: Functional Knockdown Of Polb Enables A:t Mutagenesis In Ch12supporting
confidence: 92%
See 2 more Smart Citations
“…The overall mutation frequency did not differ significantly between wild type parental (WT) and Polb knockdown CH12-F3 cells (2.1 x10 -3 vs 2.5 x10 -3 , respectively, Table I). We found that mutations at A:T base pairs were infrequent in the WT CH12-F3 cells ( 9 out of 59363 sequenced A:T bps were mutated), in agreement with a previous study (Matthews et al, 2014). In contrast, Polb knockdown CH12-F3 cells showed a considerable number of A:T mutations (23 out of 57988 sequenced A:T bps were mutated.…”
Section: Functional Knockdown Of Polb Enables A:t Mutagenesis In Ch12supporting
confidence: 92%
“…In addition, these cells accrue AID-dependent point mutations in the Ig switch μ region (Sμ) upon stimulation, similar to mouse splenic B cells Schrader et al, 2003). Strikingly, despite a high frequency of AID-dependent mutations 5' of the Sμ repetitive region, the CH12-F3 cells conspicuously lack A:T mutations for hitherto unknown reasons (Matthews et al, 2014). We hypothesized that the late gap-filling and repair activities of Polβ and LigIII diminishes entry points for Exo1, thereby suppressing A:T mutagenesis.…”
Section: Functional Knockdown Of Polb Enables A:t Mutagenesis In Ch12mentioning
confidence: 97%
See 1 more Smart Citation
“…In comparison, SHM can be induced by CSR-deficient AID variants in cells (Hwang et al, 2015; Phamet al, 2016) and by APOBEC3 homologs during retroviral infection (Halemano et al, 2014), suggesting that mutations in Ig V regions may not require all the AID features employed in CSR. Because chromatin immunoprecipitation sequencing data showed that Ig V regions may not bind AID as stably as S regions (Matthews et al, 2014b), and the assistant patch mutant R174S also causes SHM deficiency (Durandy et al, 2006; Honjo et al, 2012), we speculate that Ig V regions may only transiently recruit AID using local secondary structures like branched DNA, which do not induce AID oligomerization and stable association.…”
Section: Discussionmentioning
confidence: 93%
“…The splicing regulator PTBP2, a protein that binds AID and S region transcripts, is important for efficient CSR. Knockdown of this protein reduces the association of AID to S regions (51, 52). PTBP2 is known to regulate alternative splicing and many aspects of RNA metabolism (53), although its specific role(s) in CSR is not defined.…”
Section: Regulation Of Isotype Specificity By Transcription Of Unrearmentioning
confidence: 99%